Um estudo sobre o Ensino de Transformações Geométricas: da reforma da Matemática Moderna aos dias atuais - Luz, Vania de Andrade (2007)
This dissertation consists of a study focused on the teaching of geometrical transformations based on the analysis of exercises suggested in didactical books published since the 1960s in São Paulo State. The realization of this work is supported by an analysis with the following objectives: to examine the completion of the local mathematical organizations according to the Anthropological Theory of Didactics, by Yves Chevallard; to observe how the students main difficulties were approached, based on research by Jaime and Gutiérrez (1996) and Jahn (1998); to compare the teaching proposals of isometries and homoteties current at the time of the movement of reformation of Modern Mathematics to those which followed the publishing of the Parâmetros Curriculares Nationais (Brazilian National Curricular Standards). Initially, we proceeded to a study of the mathematical organization relative to geometrical transformations, a study in which will be examined the symmetries of elements of nature and the arts, the definitions of the main transformations that are part of the program of Ensino Fundamental (equivalent to an eight-year elementary school), besides the identification of historical elements related to the development of Geometry. After that, we will be moving on to the study of the didactical organization, in which researches about the teaching and learning of isometries were verified, as well as official texts as Curricular Guides, Proposals and Standards, besides a few aspects of the movement of reformation of Modern Mathematics in Brazil, and its relationship with the same movement in the United States and France. The analysis of the books was carried out from the grouping of exercises in types of tasks, a qualification used as much for the identification of the resolution techniques, as for the distinction of the technology appropriate to the justification of the former. Following that, we have performed a study of the set of proposed exercises, in which the above-mentioned was complied with, in the second paragraph of this abstract, as objectives of the analysis that was developed. Departing from the adopted theoretical basis, the conclusions of the research indicate that the orientations observed in each of the analyzed periods would not guarantee, per se, that important problems in the teaching of transformations were resolved. As it is known, the period correspondent to the movement of reformation of Modern Mathematics has emphasized the mathematical structure, whereas the period that followed the publishing of the Parâmetros Curriculares highlighted the relationship of isometries and homoteties with superior levels of mathematical determination. In the first case, the visibility of the mathematical work was not highlighted, while in the second one, the absence of technological elements might have compromised the completion of the mathematical organization